Verses of Shifa’: A Response to Qur'anic Verses As a Health Intervention - Azizah, Nur; Mustofa, Ahmad; Nadlir, Muhammad Abu (Ridwan Institute, 2025)
This research is based on the growing public interest in spiritually based alternative medicine, particularly the use of Qur'anic verses as a source of healing. The issues examined include how the Shifa' verses are understood and applied in the context of alternative medicine, as well as their impact on public health. This study aims to examine the response to the Shifa' verse as a health intervention, focusing on Muyasar's interpretation and the medical practice carried out by Kyai Rohman Ismadi Jam'iyah Ruqyah Aswaja in Magelang Regency. The method employed in this study is a qualitative approach, utilizing participatory interviews and observation techniques, which involve informants from among pilgrims and patients undergoing treatment and therapy. The study of the living Quran using a phenomenological approach is a primary asset in analyzing this research, drawing on the theories of transmission and transformation by Muhammad Abduh and Rasyid Ridho, the reception theory by Wolfgang Iser, and discursive Islam by Talal Asad. The results of the study show that the Shifa' verse is not only understood as a religious text, but also internalized as a source of strength and hope for patients. The practice of medicine carried out by Kyai Rohman Ismadi prioritizes the integration of spirituality and materiality, where patients experience inner peace through the healing process, facilitated by the recitation of Qur'anic verses. This study also identified an increase in public awareness about the importance of holistic health, which involves spiritual aspects. The implications of this study highlight that the response to the Shifa' verse in Tafsir Al Muyassar plays a significant role in the practice of alternative medicine, making a positive contribution to public health and inviting further discussion on the importance of integrating spiritual aspects into modern health approaches.